2000
DOI: 10.1038/sj.onc.1203699
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Bax or Bcl-2 overexpression on the ceramide-dependent apoptotic pathway in glioma cells

Abstract: Ceramide has recently been regarded as a potential mediator of apoptosis. In the present study, the e ects of Bcl-2 and Bax on the ceramide-mediated apoptotic pathways were examined in glioma cells overexpressing Bcl-2 or Bax. Etoposide, cisplatin and tumor necrosis factor-a induced apoptosis of C6 rat glioma cells which was associated with ceramide formation due to activation of neutral sphingomyelinase, followed by release of mitochondrial cytochrome c into the cytosol and activation of caspases-9 and -3. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 60 publications
2
52
1
1
Order By: Relevance
“…On the other hand, the in¯uence of proapoptotic Bax on ceramide-mediated cell death has only been indirectly studied in C6 rat glioma cells. It was shown that overexpression of Bax in these cells enhanced etoposide-induced apoptosis without a ecting ceramide formation after etoposide treatment (Sawada et al, 2000b). From their results the authors concluded that Bax promotes apoptosis regardless of ceramide formation.…”
Section: Introductionmentioning
confidence: 65%
“…On the other hand, the in¯uence of proapoptotic Bax on ceramide-mediated cell death has only been indirectly studied in C6 rat glioma cells. It was shown that overexpression of Bax in these cells enhanced etoposide-induced apoptosis without a ecting ceramide formation after etoposide treatment (Sawada et al, 2000b). From their results the authors concluded that Bax promotes apoptosis regardless of ceramide formation.…”
Section: Introductionmentioning
confidence: 65%
“…Interestingly, this effect of BEX2 is similar to the protective function of Bcl-2 overexpression against the ceramide-mediated mitochondrial apoptosis and cytochrome c release. 31,32 Moreover, BEX2 partially protected the breast cancer cells against STS-mediated mitochondrial apoptosis (Fig. 3c), which indicates that the anti-apoptotic function of BEX2 is not limited to the ceramide response.…”
Section: Discussionmentioning
confidence: 93%
“…The activities of both N-and A-SMases were determined using a mixed micelle assay system. [6][7][8] For measuring N-SMase activity, the membrane fractions (20 mg protein) were mixed with [choline-methyl- 14 C]SM (40 000 c.p.m. in 1 nmol of bovine brain SM in 0.25% Triton X-100 solubilized by sonication) in 0.1 M Tris/HCl buffer (pH 7.4) containing 6 mM MgCl 2 , and the reaction mixture was incubated for 30 min at 371C.…”
Section: Smase Assaymentioning
confidence: 99%
“…5 We previously reported the molecular mechanism by which etoposide, an anticancer drug, induces ceramide generation in human glioma cells. [6][7][8] However, the role of ceramide in radiation-induced apoptosis in gliomas remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%